Exposure to and Attitudes Regarding Transgender Education Among Urology Residents. Issue 10 (1st October 2016) - Dy, Geolani W.; Osbun, Nathan C.; Morrison, Shane D.; Grant, David W.; Merguerian, Paul A.
ABSTRACT: Introduction: Transgender individuals are underserved within the health care system but might increasingly seek urologic care as insurers expand coverage for medical and surgical gender transition. Aim: To evaluate urology residents' exposure to transgender patient care and their perceived importance of transgender surgical education. Methods: Urology residents from a representative sample of U.S. training programs were asked to complete a cross-sectional survey from January through March 2016. Main Outcome Measures: Respondents were queried regarding demographics, transgender curricular exposure (didactic vs clinical), and perceived importance of training opportunities in transgender patient care. Results: In total, 289 urology residents completed the survey (72% response rate). Fifty-four percent of residents reported exposure to transgender patient care, with more residents from Western (74%) and North Central (72%) sections reporting exposure ( P ≤ .01). Exposure occurred more frequently through direct patient interaction rather than through didactic education (psychiatric, 23% vs 7%, P < .001; medical, 17% vs 6%, P < .001; surgical, 33% vs 11%, P < .001). Female residents placed greater importance on gender-confirming surgical training than did their male colleagues (91% vs 70%, P < .001). Compared with Western section residents (88%), those from South Central (60%, P = .002), Southeastern (63%, P = .002), and Mid-Atlantic (63%, P = .003) sections less frequently viewed transgender-related surgical training as important. Most residents (77%) stated transgender-related surgical training should be offered in fellowships. Conclusion: Urology resident exposure to transgender patient care is regionally dependent. Perceived importance of gender-confirming surgical training varies by sex and geography. A gap exists between the direct transgender patient care urology residencies provide and the didactic transgender education they receive.